Le mythe de Troie en Irlande au Moyen Âge: Togail Troí et ses recensions - Szerwiniack, Olivier (Troianalexandrina, 2018)
Abstract Even though the Irish did not claim to descend from the Trojans, they became so passionate about the Trojan War that Dares' De excidio Troiae was translated and adapted into Irish under the title Togail Troí probably as early as the eleventh century, long before the other vernacular translations. This translation-adaptation was so successful in Ireland that it was rewritten and amplified several times. Thus, at least three prose versions preserved in a total of eight manuscripts dating from the mid-twelfth to the sixteenth century and an adaptation in verse have survived. After a short presentation of the eight manuscripts containing the various versions of the Irish translation and adaptation of Dares' text and a recapitulation of the main results of previous work, the article analyzes which are the possible Latin sources of the initial genealogical and mythological presentation added by the Irish adapter in the Book of Leinster version, the oldest of the eight manuscripts.